Disease activity measures at baseline predict structural damage progression: data from the randomized, controlled AMPLE and AVERT trials. (9th December 2019) - Keystone, Edward C; Ahmad, Harris A; Yazici, Yusuf; Bergman, Martin J
Abstract: Objective: Data from two double-blind, randomized, Phase III studies were analysed to investigate the ability of Routine Assessment of Patient Index Data 3, DAS28 (CRP), modified (M)-DAS28 (CRP) and Simplified or Clinical Disease Activity Indices to predict structural damage progression in RA. Methods: This post hoc analysis included data from the 2-year Abatacept vs adaliMumab comParison in bioLogic-naïvE RA subjects with background MTX (AMPLE) trial in biologic-naïve patients with active RA (<5 years) and an inadequate response to MTX, and the 12-month treatment period of the Assessing Very Early Rheumatoid arthritis Treatment (AVERT) trial in MTX-naïve patients with early RA (⩽2 years) and poor prognostic indicators. Adjusted logistic regression analysis assessed the relationship between baseline disease activity and structural damage progression (defined as change from baseline greater than the smallest detectable change) at 12 and 24 months in AMPLE and 6 and 12 months in AVERT. Areas under the receiver operating characteristic curves for the impact of baseline disease activity on structural damage progression were calculated. Results: Adjusted logistic regression analyses included all randomized and treated patients in AMPLE ( N = 646) and those who received abatacept plus MTX or MTX monotherapy in AVERT ( N = 235). Baseline Routine Assessment of Patient Index Data 3, DAS28 (CRP) and M-DAS28 (CRP) scores significantly predicted structural progression at months 12 and 24 in AMPLE ( P < 0.05) and months 6 and 12 in AVERT ( P < 0.01), and were stronger predictors than Simplified or Clinical Disease Activity Indices. Conclusion: In this post hoc analysis of two patient populations with RA, Routine Assessment of Patient Index Data 3, DAS28 (CRP) and M-DAS28 (CRP) were good at predicting structural damage. Trial registration: ClinicalTrials.gov, http://clinicaltrials.gov : NCT00929864 (AMPLE); NCT01142726 (AVERT).